Economic impacts of adopting GM crops in the United States - Lin, William; Price, Gregory; Falck-Zepeda, José B.; Fernandez-Cornejo, Jorge (Australian Farm Institute, 2004)
This study estimates the total benefit arising from the adoption of agricultural biotechnology in 1997 and its distribution among key stakeholders along the production and marketing chain. The analysis focuses on three biotech crops: herbicide-tolerant soybeans, insect-resistant (Bt) cotton, and herbicide-tolerant cotton. Adoption of these crops resulted in estimated market benefits of US$212.5-$300.7 million for Bt cotton, US$231.8 million for herbicide-tolerant cotton, and US$307.5 million for herbicide-tolerant soybeans. These benefits accounted for small shares of crop production value, ranging from 2-5%. US farmers captured a much larger share (about a third) of the benefits for Bt cotton than with herbicide-tolerant soybeans (20%) and cotton (4%). Innovators’ share ranged from 30% for Bt cotton to 68% for herbicide-tolerant soybeans. For herbicide-tolerant cotton, US consumers and the rest of the world (including both producers and consumers) received the bulk of the estimated benefits. Estimated benefits and their distribution depend on the specification of the analytical framework, supply and demand elasticity assumptions, the inclusion of market and nonmarket benefits, crops considered, and year-specific factors (such as weather and pest infestation levels)."